1999
DOI: 10.1109/84.809057
|View full text |Cite
|
Sign up to set email alerts
|

Strongly buckled square micromachined membranes

Abstract: The buckling of compressively prestressed square membranes with built-in edges is investigated experimentally and analyzed theoretically. The buckling depends weakly on Poisson's ratio and essentially is a function of the reduced prestrain, " 0 = " 0 a 2 =h 2 , where " 0 is the physical prestrain, a is the width, and h is the thickness of the membrane. As " 0 becomes increasingly negative, the membrane undergoes two symmetry breaking buckling transitions. Beyond the first transition occurring at " cr1 , the bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
54
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 19 publications
5
54
0
Order By: Relevance
“…Here the film in-plane displacement, which can have significant impacts on the film stretching energy in the postbuckling region [6,11], is not included. This study focuses only on the buckling, on which the in-plane displacement is shown to have a minor influence [1].…”
Section: Model Developmentmentioning
confidence: 99%
“…Here the film in-plane displacement, which can have significant impacts on the film stretching energy in the postbuckling region [6,11], is not included. This study focuses only on the buckling, on which the in-plane displacement is shown to have a minor influence [1].…”
Section: Model Developmentmentioning
confidence: 99%
“…A small pressure was applied to the diaphragm; the thermal loads were then slowly applied; and finally the pressure was slowly removed. This roundabout process bypasses numerical instability in the FEA model [12]. The process in this work follows a similar path and is elaborated in the procedure section.…”
Section: Figurementioning
confidence: 99%
“…The smaller diaphragms show a uniform, parabolic buckled shape for a small value of w, higher-order modes are seen as the diaphragms get larger [12].…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations